2018
DOI: 10.1002/jsfa.9142
|View full text |Cite
|
Sign up to set email alerts
|

Priming to protect maize from Fusarium verticillioides and its fumonisin accumulation

Abstract: The priming state contributed to the control of F. verticillioides development from seed infection and fumonisin accumulation in the early stage of plant growth, without affecting the final crop yield, and could reduce fungicide use and environmental contamination. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Priming is known to activate systemic defense responses only when the plant is challenged by a pathogen or is exposed to abiotic stress (Aranega-Bou et al, 2014). Since natural or synthetic chemicals and infection by pathogens can induce priming effects in plants (Aguado et al, 2019;Westman et al, 2019;De Vega et al, 2021), we hypothesize that the greater positive effect observed with the use of Sedaxane alone, and to a greater extent when in combination with Fludioxonil and Metalaxil-M and in the presence of R. solani could be ascribed to a plant response related to priming. While this hypothesis requires further investigation to clarify the possible involved mechanisms, Sedaxane in combination with Fludioxonil and Metalaxyl-M can be agronomically exploited in a dicot species such as oilseed rape to control Rhizoctonia.…”
Section: Leaf Areamentioning
confidence: 99%
“…Priming is known to activate systemic defense responses only when the plant is challenged by a pathogen or is exposed to abiotic stress (Aranega-Bou et al, 2014). Since natural or synthetic chemicals and infection by pathogens can induce priming effects in plants (Aguado et al, 2019;Westman et al, 2019;De Vega et al, 2021), we hypothesize that the greater positive effect observed with the use of Sedaxane alone, and to a greater extent when in combination with Fludioxonil and Metalaxil-M and in the presence of R. solani could be ascribed to a plant response related to priming. While this hypothesis requires further investigation to clarify the possible involved mechanisms, Sedaxane in combination with Fludioxonil and Metalaxyl-M can be agronomically exploited in a dicot species such as oilseed rape to control Rhizoctonia.…”
Section: Leaf Areamentioning
confidence: 99%
“…A study in 2019 showed that, although the fungicides procymidone and iprodione triadimenol are effective in protecting seedlings, they also possess phytotoxic effects, leading to a delay in seed germination and a reduction in the developmental speed of Allium cepa seedlings [52]. In addition to using highquality seeds, the use of fungicides to achieve high yields is a widespread agricultural practice [53][54][55][56]. The chemical treatment of seeds is one of the most effective methods of controlling both fungi and insects [37].…”
Section: Seed Disinfectionmentioning
confidence: 99%
“…Seed treatments with pesticides can neutralize potentially harmful infections (Ergin et al 2021). On the other hand, effective and sustainable alternative treatments need to be developed since the use of most chemical fungicides has been banned by the EU (Aguado et al 2019). Pre-sowing seed treatment is an important alternative method that promotes rapid and uniform germination but prevents radicle protrusion from the seed coat (Sher et al 2019).…”
Section: Introductionmentioning
confidence: 99%